Szkoły polskie i polonijne w Holandii – próba kategoryzacji - Steur, Agnieszka (Studia Edukacyjne, 2018)
According to unofficial data from the Polish Consulate in The Hague, there are currently around 30 Polish and Polonia’s schools in the Netherlands. The way they operate, both in legal and educational terms, are different. This article is an attempt to categorize them. In addition, this article characterizes the existing schools by dividing them into four categories – school consultation points linked with Polish diplomatic missions, schools associated in the Polish Schools’ Forum in the Netherlands, schools operating at parishes and non-affiliated ones. According to the Dutch Planning Office, there are currently 250,000 Poles in the Netherlands. The representatives of the Polish Consulate in The Hague estimate that there may be up to 40,000 children among people of Polish descent who live in the Netherlands. Only about 2,000 of them attend Polish and Polonia’s schools. This article is the beginning to understand why only 5% of children of Polish origin who live in the Netherlands attend schools that look after Polish language.